Impact of key parameters involved with plant-microbe interaction in context to global climate change - Shree, Bharti; Jayakrishnan, Unnikrishnan; Bhushan, Shashi (Frontiers in Microbiology, 2022)
Anthropogenic activities have a critical influence on climate change that directly or indirectly impacts plant and microbial diversity on our planet. Due to climate change, there is an increase in the intensity and frequency of extreme environmental events such as temperature rise, drought, and precipitation. The increase in greenhouse gas emissions such as CO2, CH4, NOx, water vapor, increase in global temperature, and change in rainfall patterns have impacted soil-plant-microbe interactions, which poses a serious threat to food security. Microbes in the soil play an essential role in plants' resilience to abiotic and biotic stressors. The soil microbial communities are sensitive and responsive to these stressors. Therefore, a systemic approach to climate adaptation will be needed which acknowledges the multidimensional nature of plant-microbe-environment interactions. In the last two scores of years, there has been an enhancement in the understanding of plant’s response to microbes at physiological, biochemical, and molecular levels due to the availability of techniques and tools. This review highlights some of the critical factors influencing plant-microbe interactions under stress. The association and response of microbe and plants as a result of several stresses such as temperature, salinity, metal toxicity, and greenhouses are also depicted. New tools to study the molecular complexity of these interactions, such as genomic and sequencing approaches, which provide researchers greater accuracy, reproducibility, and flexibility for exploring plant-microbe–environment interactions under a changing climate, are also discussed in the review, which will be helpful in the development of resistant crops/plants in present and future.